Realizing High‐Performance Li‐S Batteries through Additive Manufactured and Chemically Enhanced Cathodes. Issue 9 (15th August 2021) - Zheng, Matthew; Gao, Xuejie; Sun, Yipeng; Adair, Keegan; Li, Minsi; Liang, Jianneng; Li, Xiaona; Liang, Jianwen; Deng, Sixu; Yang, Xiaofei; Sun, Qian; Hu, Yongfeng; et al.
Abstract: Numerous efforts are made to improve the reversible capacity and long‐term cycling stability of Li‐S cathodes. However, they are susceptible to irreversible capacity loss during cycling owing to shuttling effects and poor Li + transport under high sulfur loading. Herein, a physically and chemically enhanced lithium sulfur cathode is proposed to address these challenges. Additive manufacturing is used to construct numerous microchannels within high sulfur loading cathodes, which enables desirable deposition mechanisms of lithium polysulfides and improves Li + and e ‐ transport. Concurrently, cobalt sulfide is incorporated into the cathode composition and demonstrates strong adsorption behavior toward lithium polysulfides during cycling. As a result, excellent electrochemical performance is obtained by the design of a physically and chemically enhanced lithium sulfur cathode. The reported electrode, with a sulfur loading of 8 mg cm ‐2, delivers an initial capacity of 1118.8 mA h g ‐1 and a reversible capacity of 771.7 mA h g ‐1 after 150 cycles at a current density of 3 mA cm ‐2 . This work demonstrates that a chemically enhanced sulfur cathode, manufactured through additive manufacturing, is a viable pathway to achieve high‐performance Li‐S batteries. Abstract : Lithium sulfur batteries are a promising next‐generation chemistry but currently face significant challenges including capacity loss owing to polysulfide shuttling and slow Li + transport. This work uses additive manufacturing in conjunction with cobalt sulfide nanocatalysts to effectively address both polysulfide shuttling and Li + transport. The outlined design demonstrates a viable strategy to elevate the performance of Li‐S batteries.